Quantitative Anatomical Study of the Supratentorial and Infratentorial “Endoscopic Keyhole” Approach to the Peripineal Region - Hao Wu; Aierpati Maimaiti; Qiang Xie; Yirizhati Aili; Mamutijiang Muertizha; Guohua Zhu; Maimaitili Mijiti; Yandong Li; Yongxin Wang (International Journal of Clinical Practice)
Background. The pineal region represents significant challenges in terms of neurosurgery. Currently, anatomical research that simulates surgery for the endoscopic keyhole approach to the pineal region is lacking. This study aims to summarize the exposure range and operational characteristics of total endoscopic surgery under the four supratentorial and infratentorial keyhole approaches, through rigorous quantitative anatomical research. We also aim to understand the surgical exposure characteristics and surgical feasibility under each approach. Method. Six wet cadaveric head specimens (a total of 12 sides) were subjected to simulated surgery with a keyhole bone window size of approximately 3 × 4 cm. The median endoscopic supracerebellar infratentorial approach (M-ESCITA), the paramedian endoscopic supracerebellar infratentorial approach (PM-ESCITA), the endoscopic occipital transtentorial approach (EOTA), and the endoscopic interhemispheric high occipital transtentorial approach (EHOTA) were used to measure the surgical path depth, maximum distance between the tentorial margins, maximum operable area, operable angle, and relative degree of freedom of each approach. Results. There was no difference in the exposure range of the surgical area. The surgical path of PM-ESCITA was the longest (p<0.001), and its horizontal operating angle was the largest (p<0.001), whereas the anteroposterior operating angle of EHOTA was the largest (p<0.001). The maximum operational area of M-ESCITA was the largest in the pineal region (p<0.01), whereas that of EHOTA was the largest in the tetrapod region (p<0.001). M-ESCITA had the highest relative degree of freedom during surgery at the pineal gland level (p<0.001), PM-ESCITA at the splenium of the corpus callosum (p<0.01), and EHOTA at the corpora quadrigemina (p<0.001). Conclusions. Each of the four endoscopic keyhole approaches has its own advantages. Through anatomical research, doctors can train themselves and master the differences in surgical procedures through different approaches. The choice of approach and surgical challenge are dependent on the microsurgical techniques employed by the surgeon. A balance between minimally invasive and safe endoscopic surgery should be pursued.